A conservative approach to pediatric mandibular fracture management: Outcome and advantages - Amit Khatri; Namita Kalra (Wolters Kluwer Medknow Publications, 2011)
Pediatric mandibular fractures are rare and their treatment remains controversial. Management is extremely complicated in mixed dentition as it is inherently dynamic and unstable. Treatment options include soft diet, intermaxillary fixation with eyelet wires, arch bars, circummandibular wiring, or stents. Alternative options include open reduction and internal fixation through either an intraoral or extraoral approach. This case report describes and evaluates the conservative technique of acrylic splint in the treatment of pediatric mandible fracture in a 12-year-old female child. The patient with isolated mandibular fracture was treated with acrylic splint and interdental wiring followed by evaluation of clinical and radiographic healing as well as the somatosensory status. Patient demonstrated clinical union to her pre-injury occlusion by three to four weeks. Panoramic finding supported the finding of clinical examination throughout the study. High osteogenic potential of the pediatric mandible allowed conservative management to be successful in this case.